HEGEMONI ESTETIKA POSTCOLONIAL DALAM REPRESENTASI IKLAN Dl MEDIA MASSA CETAK INDONESIA KONTEMPORER - Kasiyan Kasiyan (Humaniora, 2012)
This study is aimed at describing postcolonial aesthetic hegemony in the advertisements of contemporary Indonesian printed mass media, focusing on three main issues: 1) their signifiers and signified representations; 2) various factors underlying the strength of postcolonial aesthetics; and 3) strategies of cultural resistance policy to build possible counter-postcolonial aesthetics awareness. The main approach of this study is postcolonial, supported by other relevant approaches such as semiotics and history. The main instrument of this study is the researchers themselves as the human instruments. The research data are in the forms of advertisements from printed media, namely: Tempo, Femina, and Kartini in the period of 2007-2009. The data are analyzed by using descriptive qualitative techniques. The results of this study show that I) there are three dominant signifier hegemony representations of Western aesthetics in the print media advertising in contemporary Indonesia, associated with obsessions of a) Western physical appearance or Indo; b)Western whiteness; and c) the use of English; 2) these phenomena are the results of the existence of Indonesians' strong construction of colonialism syndrome; 3) one of the strategies to build possible counter-postcolonial aesthetics is by improving awareness on local cultures as the foundation to build national culture and identity